1984
DOI: 10.1044/jshr.2703.329
|View full text |Cite
|
Sign up to set email alerts
|

Management of Sentence Production Demands

Abstract: This study examined the effects of variations in language complexity on young children's phonological accuracy and consistency of target words. A more general intent was to understand better the way in which developmental level and children's tolerance of speech variability influenced the management of processing demands. Seven children aged 22–34 months were seen six times over a 4-month period. During these sessions, children were presented with an elicited imitation task consisting of 18 stimulus words, eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Interactions between the neural systems responsible for language and those responsible for speech motor control have been frequently observed. In typically developing children, for example, increases in syntactic complexity and utterance length are associated with articulatory simplifications (Prelock & Panagos, 1989), increased articulatory error production (Kamhi, Catts, & Davis, 1984), and increased speech motor variability (Maner, Smith, & Grayson, 2000). Additionally, typically fluent children as well as children who stutter demonstrate higher disfluency rates under conditions of increased length and syntactic complexity (Logan & Conture, 1997;Ratner & Sih, 1987;Silverman & Ratner, 1997;Yaruss, 1999;Zackheim & Conture, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Interactions between the neural systems responsible for language and those responsible for speech motor control have been frequently observed. In typically developing children, for example, increases in syntactic complexity and utterance length are associated with articulatory simplifications (Prelock & Panagos, 1989), increased articulatory error production (Kamhi, Catts, & Davis, 1984), and increased speech motor variability (Maner, Smith, & Grayson, 2000). Additionally, typically fluent children as well as children who stutter demonstrate higher disfluency rates under conditions of increased length and syntactic complexity (Logan & Conture, 1997;Ratner & Sih, 1987;Silverman & Ratner, 1997;Yaruss, 1999;Zackheim & Conture, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, not all studies have demonstrated all predicted interactions (e.g., Kamhi et al, 1984;Streim and Chapman, 1987). Despite this, a limited capacity, interactionist perspective of language impairment has remained central to assessment and intervention for language impairments in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally assumed that linguistically more complex forms are more challenging for children to acquire or produce (Bloom, 1970;Brown & Hanlon, 1970;Kamhi, Catts, & Davis, 1984). In particular, researchers have noted that words with simple syllable structures appear earlier in development, with 1 According to some accounts of syllable structure, liquids and nasals followed by -s can be syllabified as part of a branching coda, whereas obstruent+s clusters, which violate the sonority sequencing principle, must be syllabified as a singleton coda consonant plus an -s appendix at the higher level of the syllable (Selkirk, 1982;see Kirk & Demuth, 2005, for discussion).…”
Section: A Phonological Approachmentioning
confidence: 99%